STRATEGI KOMUNIKASI KETERBUKAAN INFORMASI PUBLIK TERHADAP PENCAPAIAN PROGRAM CSR PADA PT MIFA BERSAUDARA ACEH BARAT - Zul Eman Man; Fiandy mauliansyah (JIMSI: Jurnal Ilmiah Mahasiswa Ilmu Komunikasi, 2021)
Corporate Social Responsibility (CSR) is fostering relationships between the community and the company to attract public sympathy for sustainable development in the company's operational areas. To minimize the opportunity for conflict in the community, the company needs to develop a communication strategy for public information disclosure related to the implementation of CSR programs in the company's operational area. This scientific karva is a descriptive study with a qualitative approach using survey methods. Data collection was carried out during the student internship period for one semester (6 months) starting from February - August 2021 at the Department of Group External Relations, CSR, and Corporate Communication of PT. Mifa Bersaudara. Disclosure of public information is carried out in accordance with Law No. 14 of 2008, concerning Public Information Disclosure, one of the Indonesian legal products issued in 2008 and promulgated on April 30, 2008 so that it comes into force two years after its promulgation. Public Relations in the 7-pillar-based Corporate Social Responsibility (CSR) program is a strategy to build public openness communication carried out by public relations at PT Mifa Bersaudara. The West Aceh Regency Corporate Social and Environmental Responsibility Forum (TJLSP) plays an effective role in a sustainable and sustainable process of public information disclosure.